Features of Valence Electron Density Distribution in Zr–H and Zr–He; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Lopatina O. V. Oksana Valerievna; Svyatkin L. A. Leonid Aleksandrovich; Koroteev Yu. M. Yuri Mikhailovich; Chernov I. P. Ivan Petrovich (Plasma, Microwave, Ion, Electron and Isotope Technologies, 2015)
Title screen